The Influence of Hadith Memes on Honesty on Instagram Public Interest - M. Basyir Faiz Maimun Sholeh (An-Nisa' Journal of Gender Studies, 2022)
In Indonesia, honesty does not thrive. The enormous number of cases of corruption and deception strongly demonstrate this. However, many people keep promoting the significance of honesty in a variety of ways, such as publishing hadith memes on honesty on Instagram. At least four accounts have done it in different ways. One of them includes both the hadith text and its translation, while the others merely provide the translation. The objective of this research is to determine which type of meme has the most influence in society, especially in Indonesia. This research is presented using descriptive-analytic methods. The qualitative approach would identify and analyze society's responses to each meme type to achieve the aforementioned goal. Once both sides are compared, the second one has greater interest than the first. In other words, Indonesians are unconcerned about the text of the hadith as long as they understand its message.